Pengalaman Emosional dan Pola Kepribadian Mahasiswa Dengan Social Anxiety Disorder Dalam Situasi Sosial - Naya Sofia Dinanti; Sri Nurhayati Selian (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to deeply understand the emotional experiences and personality patterns of students with Social Anxiety Disorder dealing with various social situations. Students, as individuals in the early adult stage, are required to actively interact in academic environments. However, for those experiencing social anxiety, these demands can be a source of pressure that affects their emotional state and behavior. This study used a qualitative approach with a phenomenological method to explore the subjective experiences of the participants. The research subjects consisted of three students selected through purposive sampling technique with the criteria of having a tendency towards social anxiety. Data were collected through in-depth semi-structured interviews, then analyzed through the stages of data reduction, data presentation, and conclusion drawing, and its validity was tested using triangulation. The results showed that students experienced anxiety, fear of negative judgment, low self-confidence, and a tendency to avoid social situations. Physical symptoms such as heart palpitations, sweating, and difficulty speaking also appeared. In addition, a personality pattern was found that tended to be introverted and sensitive to the judgments of others. This condition impacted academic activities and social relationships. This research is expected to provide a basis for developing effective interventions and mentoring.